Perbedaan Gender dalam Persepsi Harga, Promosi, dan Online Review Produk Pakaian Erigo terhadap Niat Pembelian Online - Endang Hariningsih; R. Nur Budi Setiawan; Eni Munarsih; Muhammad Taufiqur Rahman (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
This research have purpose to finding the direct influence between price perceptions, online reviews, and online promotions on the online purchase intention of Erigo products. In addition, gender variable testing is also carried out as a moderation. The data used was primary data from 230 respondents to students in Yogyakarata. The research used quantitative analysis methods using Likert-scale instruments. And than, used Structural Equation Modeling analysis tools using SmartPLS 3.0 for Measurement Model and Structural Model testing. The results of the analysis find the influence of variables of price perception and promotion on online purchase intentions. Meanwhile, online reviews have no effect on online purchase intentions. As for after moderation testing, only the relationship between price perception and purchase intention was significantly moderated by gender. These findings offer implications for marketers to pay attention to product pricing to match price and quality and be able to show product quality signals. Finally in the conclusion section are shown the implications, limitations and future direction of the study